2014
DOI: 10.1007/s00424-014-1561-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ATP secretion via volume-regulated anion channels by sphingosine-1-phosphate in RAW macrophages

Abstract: We report the activation of outwardly rectifying anion currents by sphingosine-1-phosphate (S1P) in the murine macrophage cell line RAW 264.7. The S1P-induced current is mainly carried by anions, because the reversal potential of the current was shifted by replacement of extracellular Cl(-) by glutamate(-) but not when extracellular Na(+) was substituted by Tris(+). The inhibition of the current by hypertonic extracellular or hypotonic intracellular solution as well as the inhibitory effects of NPPB, tamoxifen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 78 publications
1
46
0
Order By: Relevance
“…The release of ATP through volume regulated channels has been proposed long time ago in hepatoma 39 and endothelial cells 52 and more recently in astrocytes and Raw macrophages 44, 53, 54 . Our conclusion that ATP is released by microglia under hypotonic stimulation is based on severeal lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The release of ATP through volume regulated channels has been proposed long time ago in hepatoma 39 and endothelial cells 52 and more recently in astrocytes and Raw macrophages 44, 53, 54 . Our conclusion that ATP is released by microglia under hypotonic stimulation is based on severeal lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…, Burow et al . ). This unique permeation profile of VRAC is important for its role in non‐synaptic cellular communication which modulates neuronal excitability and synaptic activity in the brain.…”
Section: Basic Biophysics Of Vracmentioning
confidence: 97%
“…Volume‐independent activation of VRAC is also induced by sphingosine‐1‐phosphate, which is generated by S‐kinase activated by bacterial lipopolysaccharide (LPS), PDGF, TNF α , thrombin, IgE‐bound antigen and importantly ATP (Burow et al . ).…”
Section: Mechanisms Of Vrac Activation and Modulationmentioning
confidence: 97%
“…Electrophysiological studies already showed that hypotonicity‐induced Cl − currents of HaCaT cells are sensitive to various Cl − channel inhibitors . Different efficiencies and incomplete blocking have been described for several VRAC inhibitors in many cell types including HaCaT cells and NHEKs . In our hsYFP‐based measurements in HaCaT cells, CBX almost completely blocked hypotonicity‐induced I − influx (90%).…”
Section: Discussionmentioning
confidence: 53%
“…[11] Different efficiencies and incomplete blocking have been described for several VRAC inhibitors in many cell types including HaCaT cells and NHEKs. [11,33,41,42] In our hsYFP-based measurements in HaCaT cells, CBX almost completely blocked hypotonicity-induced I − influx (90%). A comparable degree of inhibition (80%) of VRAC-mediated Cl − currents was reported for CBX in cultured rat cortical astrocytes.…”
Section: Discussionmentioning
confidence: 84%